HUBUNGAN ANTARA STATUS SOSIAL EKONOMI KELUARGA DENGAN STATUS GIZI ANAK USIA SEKOLAH DI SD NEGERI 14 NAN SABARIS - YUSRA, REZKI YETI; ZALMADANI, HENDRO; RAHMIWATI, RAHMIWATI; SEVENTRI, EDWAR (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Nutritional status describes the balance between the body's need for nutrients to maintain life, growth, development, maintenance of normal body functions and for energy production and other nutrient intake. The purpose of this study was to determine the relationship between family socio-economic status and the nutritional status of school-age children at SD Negeri 14 Nan Sabaris. This study used a descriptive analytical research type with a research design using a Cross Sectional approach. The population in this study was The population in this study were students of SD Negeri 14 Nan Sabaris District, Padang Pariaman Regency. Samples were taken using the simple random sampling method, or a simple random design. The sample in this study was 61 respondents. The univariate analysis results are displayed in the form of a frequency distribution of economic and nutritional status. Bivariate analysis using chi square at α = 0.05%. The results of the study obtained a high socio-economic status category of 18 people (29.5%), moderate there were 9 people (14.8%) and low as many as 34 people (55.7%). While the nutritional status of school children in the normal category was 30 people (49.2%) and thin as many as 31 people (50.8%). In conclusion, there is a significant relationship between socioeconomic status and nutritional status of school children at SDN 14, Nan Sabaris District.